Інформаційна та математичні моделі проточної частини в задачах оптимального проєктування турбоблоку - Шерфедінов, Різа Бахтіярович; Усатий, Олександр Павлович; Авдєєва, Олена Петрівна (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянуті питання удосконалення структурно-топологічного формування інформаційної моделі проточної частини (ПЧ) парової турбіни з метою її використання в задачах оптимального проєктування турбоблоків. Додано новий ієрархічний рівень "Відсік", що дозволило зв'язати в єдиному інформаційному просторі параметри ПЧ та решти обладнання турбоблоку та надало можливість ставити і розв'язувати задачі оптимального проєктування турбоблоків. Удосконалена одновимірна модель процесів в ПЧ, що дозволяє моделювати протікання процесів в ПЧ турбіни від відсіку до відсіку (повідсікове моделювання процесів в ПЧ з заданими параметрами пари між відсіками). Удосконалена математична модель процесів в ПЧ узгоджена з удосконаленою інформаційною моделлю ПЧ і є однією із складових підсистеми оптимального проєктування САПР "Турбоагрегат". Проведені тестові порівняльні розрахунки ПЧ циліндрів парових турбін виконані з використанням алгоритмів створених на основі двох математичних моделей: вихідної та удосконаленої. Підтверджено хороший збіг результатів.

The issues of improving the structural-topological formation of the information model of the flow path of a steam turbine with the aim of using it in the problems of optimal design of turbine blocks are considered. A new hierarchical level "Compartment" has been added, which made it possible to link in a single information space the parameters of the frequency converter and the rest of the equipment of the turbine unit and made it possible to set and solve the problems of optimal design of turbine blocks. An improved one-dimensional model of the processes in the frequency converter, which allows simulating the course of processes in the frequency converter of a turbine from compartment to compartment (sub-section modeling of processes in the frequency converter with given steam parameters between the compartments). The improved mathematical model of the processes in the frequency converter is coordinated with the improved information model of the frequency converter and is one of the components of the optimal design subsystem of the "Turboagregat" CAD system. The performed test comparative calculations of the FC of steam turbine cylinders were carried out using algorithms created on the basis of two mathematical models: the original and the improved one. Good agreement was confirmed. Insignificant differences in thermogasdynamic parameters in the cross-sections between the rims of the inverter, obtained according to the original and improved models, are noted. Small deviations in the results are mainly caused by the need to use in the improved model the formulation of the problem with the given steam parameters in front of each compartment and the value of the mass flow rate to the head of each compartment. The fulfillment of the boundary conditions was ensured by a corresponding change in the effective angle of the nozzle grate of the first stage of each compartment.
Information and mathematical models of the flow part in the problems of optimal design of a turboblock
Keywords: турбоблок; математична модель; парова турбіна; проточна частина; інформаційна модель; turbo block; steam turbine; flow path; information model; mathematical model